Defects in Disneyland: Quality Control as a Two-Part Tariff - Braverman, Avishay; Guasch, J. Luis; Salop, Steven (Review of Economic Studies, 1983)
This paper shows that firms endowed with monopoly power can utilize an optional service contract form of guarantee as an instrument for effecting a surplus extracting two-part tariff. The monopolist finds it optimal to produce, guarantee and replace defective units, even if a zero defect rate could be achieved at no additional production cost. It is also shown that the price per unit is greater than the “effective” marginal cost; it may even be higher than the pure monopoly price. Moreover the monopolist is unable to extract all of the consumers surplus. Thus, that optional service contract policy can provide an effective yet defensible form of price discrimination as an alternative to possible illegal tie-ins, quantity discounts and simple two-part tariffs.